Enhanced Geothermal Systems and other Deep Geothermal Applications throughout Europe: The MEET Project (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The MEET Special Issue aims at showing the gains in geothermal energy that can be achieved using a variety of techniques, depending on the geological setting of the underground. Among the list of exploitation concepts, enhanced geothermal systems (EGS) are particularly interesting, as their application is much less dependent of the underground setting, allowing, in turn, a large geographical deployment and market penetration in Europe. The challenges of EGS are multiple in terms of investment costs, the testing of novel reservoir exploitation approaches with an inherent risk of induced seismicity, and the presence of aggressive geothermal brines, damaging infrastructures. The conversion of oil wells or coproduction of heat or electricity together with oil is also addressed. This Special Issue summarizes the output of the H2020 MEET project based on laboratory experiments, geological field works on high-quality analogues, advanced reservoir modeling, the development of a decision-maker tool for investors and specific demonstration activities, such as chemical stimulation or the innovative monitoring of deep geothermal wells, and the production of electrical power via small-scale binary technology tested in various geological contexts in Europe.